Spatial marine zoning for fisheries and conservation. Issue 7 (20th August 2009) - Klein, Carissa Joy; Steinback, Charles; Watts, Matthew; Scholz, Astrid J; Possingham, Hugh P
Abstract : Protected areas are an effective tool for reducing biodiversity loss. Current legislation distinguishes various types of marine protected areas, each allowing different levels of resource extraction. However, almost all of the theory for spatial conservation planning is focused on identifying no‐take reserves. The current approaches to zoning for multiple types of protected areas could result in suboptimal plans in terms of protecting biodiversity and minimizing negative socioeconomic impacts. We overcame these limitations in the first application of the multizone planning tool, Marxan with Zones, to design a network of four types of protected areas in the context of California's Marine Life Protection Act. We have produced a zoning configuration that entails mean value losses of less than 9% for every fishery, without compromising conservation goals. We also found that a spatial numerical optimization tool that allows for multiple zones outperforms a tool that can identify one zone (ie marine reserves) in two ways: first, the overall impact on the fishing industry is reduced, and second, a more equitable impact on different fishing sectors is achieved. Finally, we examined the tradeoffs between representing biodiversity features and impacting fisheries. Our approach is applicable to both marine and terrestrial conservation planning, and delivers an ecosystem‐based management outcome that balances conservation and industry objectives.